The Worldwide Spread of the International Baccalaureate: Cosmopolitanism and (Global) Inequalities - Schippling, A.; Abrantes, P. (XX ISA World Congress of Sociology: Resurgent Authoritarianism: Sociology of New Entanglements of Religions, Politics, and Economics, 2023)
The organization International Baccalaureate, a nonprofit educational foundation, and its network of IB World Schools, has greatly expanded, especially since 2000, from 1,052 schools in 2000, to 3,035 schools in 2010, and 5,500 schools in 2022, across 160 countries (IB 2022). It offers an alternative curriculum, recognized by almost all countries in the world. Legitimated by values such as cosmopolitanism, global citizenship and cultural openness, this rapid growth in recent decades is a phenomenon which is intertwined with spreading economic and education policy globalization. Especially in countries of the global south, it may be understood as a (distinction) strategy for the social reproduction of upper- and new middle-class families, through detachment from national systems and introduction to a global elite. Firstly, our paper outlines tendencies of the worldwide evolution of IB, employing a global comparative approach. Secondly, we discuss some results from an analysis of the implementation of IB in the metropolitan areas of three Portuguese-speaking countries in different continents: Lisbon (Portugal), São Paulo (Brazil) and Maputo (Mozambique). These analyses include data provided by IB (2022) as well as all websites of IB schools in these regions and other IB-related websites and documents. Based on previous research in Portugal (e.g. Schippling & Abrantes 2022), the aim of our paper is to present original data from an ongoing comparative project on the global development of IB schools, focused on how they deal with cultural diversity, social inequalities and political participation. References: IB (International Baccalaureate) 2022. Facts and figures. Retrieved from https://www.ibo.org/about-the-ib/facts-and-figures (accessed 20 Sep 2022). Schippling, A., and P. Abrantes 2022. Analysing biographies in transnational educational spaces: transitions to higher education of alumni from an IB school in Lisbon. Globalisation, Societies and Education. Advance online publication: 1–12.